Sri Lanka, glimpses of an Island culture - Prematilleka, Leelananda; Wikramagamage, Chandra; Madhyama Saṃskr̥tika Aramudala (Sri Lanka). ([Colombo] Central Cultural Fund Publication, 2003)
Cultural history of Sri Lanka.
"CCF publication 337"--T.p. verso.
Includes bibliographical references (p. 101).
Keywords: Sri Lanka -- Civilization